Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/nu14010179
|View full text |Cite
|
Sign up to set email alerts
|

Lean Mass Improvement from Nutrition Education and Protein Supplementation among Rural Indian Women Living with HIV/AIDS: Results from Cluster Randomized Factorial Trial at 18-Month Follow-Up

Abstract: Loss of lean muscle mass impairs immunity and increases mortality risk among individuals with HIV/AIDS. We evaluated the relative contributions of protein supplementation and nutrition education on body composition among 600 women living with HIV/AIDS in rural Andhra Pradesh, India. We conducted a cluster randomized controlled 2 × 2 factorial trial lasting six months with follow up at twelve and eighteen months. Interventions occurred in the Nellore and Prakasam regions of Andhra Pradesh by trained village wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…In terms of morbidity, we observed that, of the four studies that examined the effect of nutrition counselling on CD4 count, nutrition counselling led to significant improvements in CD4 count in two of the studies. The results of our meta-analysis also showed that nutrition counselling improved CD4 count by 55 cells/μL after 6 months, similar to reports from other studies [37]. A change in CD4 count of $55 cells/μL is less likely to alter treatment plans and is within the limits of error of many CD4 instrument evaluations [39].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In terms of morbidity, we observed that, of the four studies that examined the effect of nutrition counselling on CD4 count, nutrition counselling led to significant improvements in CD4 count in two of the studies. The results of our meta-analysis also showed that nutrition counselling improved CD4 count by 55 cells/μL after 6 months, similar to reports from other studies [37]. A change in CD4 count of $55 cells/μL is less likely to alter treatment plans and is within the limits of error of many CD4 instrument evaluations [39].…”
Section: Discussionsupporting
confidence: 88%
“…Two studies examined other anthropometric measures (Table 4). The first was the 2 Â 2 factorial design cluster RCT conducted in Andhra Pradesh, India, with a follow-up until 18 months [7,37]. Nutrition counselling significantly increased lean mass by 6 months among those who also received supplementation by 2.4 kg (95% CI: 1.3-3.5), but not among those who did not also receive supplementation (MD: 0.5, 95% CI: À0.5-1.5).…”
Section: Weight and Other Anthropometric Measuresmentioning
confidence: 99%